2021
DOI: 10.1371/journal.pone.0244593
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA-Seq analysis unfolds a complex regulatory network imparting yellow mosaic disease resistance in mungbean [Vigna radiata (L.) R. Wilczek]

Abstract: Yellow Mosaic Disease (YMD) in mungbean [Vigna radiata (L.) R. Wilczek] is one of the most damaging diseases in Asia. In the northern part of India, the YMD is caused by Mungbean Yellow Mosaic India Virus (MYMIV), while in southern India this is caused by Mungbean Yellow Mosaic Virus (MYMV). The molecular mechanism of YMD resistance in mungbean remains largely unknown. In this study, RNA-seq analysis was conducted between a resistant (PMR-1) and a susceptible (Pusa Vishal) mungbean genotype under infected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 73 publications
3
28
0
Order By: Relevance
“…[ 23 ]. For PHI-base analysis, Dasgupta et al [ 24 ] identified many transcripts as gene homologues which were found to be associated with both compatible and incompatible host-pathogen interactions (reduced virulence, unaffected pathogenicity, loss of pathogenicity, etc.) which is similar to what we have recorded in lentil when infected with Rhizoctonia .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 23 ]. For PHI-base analysis, Dasgupta et al [ 24 ] identified many transcripts as gene homologues which were found to be associated with both compatible and incompatible host-pathogen interactions (reduced virulence, unaffected pathogenicity, loss of pathogenicity, etc.) which is similar to what we have recorded in lentil when infected with Rhizoctonia .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, comparative RNA-seq analysis has become a comprehensive approach for the identification of DEGs under infected and control conditions that help in the identification of the precise gene networks that are operating under infection, especially in the susceptible genotype [ 20 , 21 ]. This method has been widely applied to identify the plant-pathogen interactions in several crops such as rice [ 22 ], peanut [ 23 ], mungbean [ 24 ], and lentil [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primer sets used for qRT-PCR are listed in Table S4. The transcript levels of selected V. radiata DEGs were normalized to the expression of the housekeeping gene β-actin as previously mentioned [39][40][41][42][43][44] .…”
Section: Qrt-pcr Of Degsmentioning
confidence: 99%